GUT-ISOLATED BACTERIA AND BIOCHEMICAL COMPOSITION ISOLATED FROM EDIBLE CRAB SPECIES IN MANAPAD, INDIA (International Journal of Food and Nutritional Sciences, 2022)
Crabs constitute an important resource in the marine fishery in India and contributed an overall average of 9.6% to the total crustacean landings from 1975-to 2020. Many species of crabs are exploited alonIndia’s east and west coasts, mainly in trawls as by-catch and as a targeted resource in a gill net in some regions. In Tamil Nadu, the hitherto dominating species Portunus pelagicus (30.7%) has been overtaken by Portunus sanguinolentus (33.3%) with a marginal increase registered in the landings. Crabs proteins are rich in essential amino acids (EAA). Muscle proteins are grouped into three categories based on location in the skeletal muscle and solubility sarcoplasmic, stromal, and myofibrillar proteins. The survival, health, growth, and efficient feed utilization of fish depend on the nutritional value of feedstuff. Fish, like any other animal, do not have a nutritional requirement of protein per se but require a well-balanced mixture of indispensable or essential amino acids (EAA) and dispensable or nonessential amino acids. Using the 16S ribosomal RNA sequences (Bacteria) database and the sequences of purified PCR products from the final 2 isolates (ON248499 and ON248500), the National Center for Biotechnology Information's (NCBI) BLAST programme. The results of the current analysis showed that P.sanguinolentus tissue has the most protein compared to other tissues. The findings of those who claimed that P.pelagicus had has a decent amount of protein match well with those of the current investigation, the level of total lipid in the body tissues of crab Portunus pelagicus and Portunus sanguinolentus is (0.3% and 2.3%) As a result, the current study aimed to increase seafood intake among the general public by emphasising the nutritional importance of seafood, particularly crabs, in the local community.